Filler reinforced polydimethylsiloxane-based vitrimers. (20th May 2019) - Spiesschaert, Yann; Guerre, Marc; Imbernon, Lucie; Winne, Johan M.; Du Prez, Filip
Abstract: Vitrimers are a type of covalent adaptable networks that use an associative mechanism resulting in the ability to be thermally processed without losing their network integrity, even at elevated temperatures. Here we describe the synthesis of vinylogous urethane-based thermally stable, reinforced polydimethylsiloxane vitrimers with a special emphasis on the influence of the filler's acidic or basic functionalization on relaxation times. The vitrimer design is based on a straightforward condensation reaction between amino terminated polydimethylsiloxane and a trifunctional acetoacetate. The addition of fillers improves the mechanical properties, reduces the soluble fraction, preserves processability and, depending on the amount of filler added, maintains the ability to be recycled, without loss of properties. Furthermore, the relaxation times can be slightly tuned by using acidic or basic fillers, whilst keeping the corresponding material properties. These results show that fillers can be used as both reinforcing agents and catalysts in vinylogous urethane vitrimer systems. Graphical abstract: Image 1 Highlights: Thermally stable vinylogous urethane PDMS vitrimers were obtained. PDMS vitrimers were successfully reinforced with fillers and maintained recyclability. The filler's functionality displayed a direct influence on the stress-relaxation speed. Fillers could be used as reinforcing agents and catalysts for vitrimers.